TRP Channels Regulation of Rho GTPases in Brain Context and Diseases - Lavanderos, Boris; Silva, Ian; Cruz, Pablo; Orellana-Serradell, Octavio; Saldías, María Paz; Cerda, Oscar (Frontiers in Cell and Developmental Biology, 2020)
Neurological and neuropsychiatric disorders are mediated by several pathophysiological mechanisms, including developmental and degenerative abnormalities caused primarily by disturbances in cell migration, structural plasticity of the synapse, and blood-vessel barrier function. In this context, critical pathways involved in the pathogenesis of these diseases are related to structural, scaffolding, and enzymatic activity-bearing proteins, which participate in Ca2+- and Rho GTPases-mediated signaling. Rho GTPases are GDP/GTP binding proteins which regulate the cytoskeletal structure, cellular protrusion, and migration. These proteins cycle between GTP-bound (active) and GDP-bound (inactive) states due to their intrinsic GTPase activity and their dynamic regulation by GEFs, GAPs, and GDIs. One of the most important upstream inputs that modulate Rho GTPases activity is Ca2+ signaling, positioning ion channels as pivotal molecular entities for Rho GTPases regulation. Multiple non-selective cationic channels belonging to the TRP family participate in cytoskeletal-dependent processes through modulation of Ca2+-mediated modulation of Rho GTPases. Moreover, these ion channels have a role in several neuropathological events such as neuronal cell death, brain tumor progression and strokes. Although Rho GTPases-dependent pathways have been extensively studied, how they converge with TRP channels in the development or progression of neuropathologies is poorly understood. Herein, we review recent evidence and insights that link TRP channels activity to downstream Rho GTPase signaling or modulation. Moreover, using the TRIP database, we establish associations between possible mediators of Rho GTPase signaling with TRP ion channels. As such, we propose mechanisms that might explain TRP-dependent modulation of Rho GTPases as possible pathways participating in the emergence or maintenance of neuropathological conditions.